Appraisal of different attributes of fish community in Andharmanik River of coastal Bangladesh and socio-economic conditions of fishermen - Dulon Roy; Nishat Binte Didar; Smita Sarker; Md. Arafat Rahman Khan; Gulshan Ara Latifa (Heliyon, 2022)
The purpose of this study was to determine the fish species composition and appraise the status of fish diversity through sampling in six sample locations and to observe the socio economic conditions of the fishermen surrounding the river during the study period. There were 81 fish species found, classified into 13 orders, 40 families, and 69 genera. The most dominant order was Perciformes (55.42 %), followed by Clupeiformes (20.44 %), Cypriniformes (8.96 %), Siluriformes (8.13 %), and others (7.05%). To illustrate the species diversity, fish species richness and evenness in sampling areas, indices of fish community viz. Shannon-Wiener's Index (H), Simpson's Dominance Index (D), Simpson's Diversity Index (1-D), Margalef's Index (d) and Gibson's Evenness (€) were used and 3.29–3.48, 0.05–0.069, 0.93–0.95, 6.88–8.43 and 0.39–0.49 respectively were the overall values of the indices. S1 station is significantly differ in species richness from the rest of the five stations (P < 0.05). The analysis of similarity (ANOSIM) displayed significant (P-value < 0.05) variations in fish community among stations and months. In compliance with similarity percentage (SIMPER) analysis, 35.8% similarities were observed among the fish species from different stations, while 59.36% similarities were detected among the fish species from different months. One species is critically endangered (CR), three species are nearly threatened, eight species are endangered (EN), and eight species are vulnerable among the 81 fish species recorded at various sampling locations. The socioeconomic conditions of fishermen were determined on the basis of a personal interview and focus group discussion. Unfair fishing practices as well as environmental instabilities such as reduced water volume, increased sedimentation, water abstraction, and pollution have ravaged fish habitat and diminished fish diversity over time. As a result, fish preservation in the Andharmanik River has become imperative, and an integrated management plan should be designed and executed as soon as possible.